A secure and efficient DSSE scheme with constant storage costs in smart devices - Weiwei Yan; Sai Ji (Cyber Security and Applications)
With the continuous development of the Internet of Things (IOT) and cloud computing, smart devices are playing an increasingly important role in users’ daily life. Dynamic searchable symmetric encryption (DSSE) schemes are popular on smart devices because of their efficient retrieval performance and low computational overhead. Traditional DSSE with forward update privacy and backward security can resist file injection attack and statistical inference attack. However, it is high cost and not suitable for smart devices due to large local storage and low storage capacity. To achieve forward update privacy, we design a novel index structure called RC-II (Inverted Index with Retrieve Control) for search control which improves the security of DSSE. Besides, we combine on and off-chain to decrease client’s local storage to a constant. Specifically, we transfer a significant amount of local overhead to the service peers off blockchain. We solve the trust problem between the client and the service by putting authentication data on blockchain. Compared with the state-of-the-art schemes, our scheme has a constant client storage overhead and an excellent retrieval performance which provides guarantee for smart devices under IOT environment.